Hubungan Dukungan Suami, Pengetahuan Dan Sikap Terhadap Pola Hubungan Seksual Pada Ibu Masa Premenopause Di Puskesmas Labuan Tahun 2022: Relationship of Husband's Support, Knowledge and Attitude to Patterns of Sexual Relations in Perimenopausal Mothers at Labuan Health Center in 2022 - Vidayawati (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Perimenopause is a natural cycle, but apparently not all women can accept this well. There are women who feel anxious before menopause. This is because when a woman is about to enter menopause, there are many changes in her, and women who are not ready for these changes will perceive menopause as something negative that will interfere with their lives. Methods: The purpose of the study was to determine the frequency distribution and the relationship of husband support, knowledge, and attitudes toward sexual relations patterns in premenopausal women at the Labuan Health Center. The research methodology is descriptive-analytic with a cross-sectional approach Results: Univariate description shows that most of the respondents who have good husband support as many as 49 people (87,5%) have good knowledge as many as 49 people (87,5%). 50 people (89,3%) have a good attitude. And those who have a good sexual relationship pattern are 41 people (73,2%). This is obtained from the results of statistical tests on the husband support variable p-value (0,000) < (0,05), knowledge variable p-value (0,012) < (0,05) sexual relationship pattern variable p-value (0,004) < (0,05) then H0 is rejected and Ha is accepted. Discussion: The suggestions for Health Center can provide direction regarding the importance of husband support, knowledge, and attitudes for perimenopausal mothers.